Visual Analogue Scale (VAS) and Self Leg Raised (SLR) cores following traditional massage “Tusukan Siku” in chronic Lower Back Pain (LBP) patients: MRI diagnostic - Othman, Che Noriah; Che Lamin, Roz Azinur; Farooqui, Mariam (2013)
Low Back Pain (LBP) is the most common condition in musculoskeletal disease. Previous epidemiologic studies have indicated that approximately 70-90% of the population experience LBP at one time or another in their lives. Use of traditional and alternative therapies including massage is common among different cultures to treat lower back pain but not proven clinically. The aim of this study is to evaluate the effectiveness of Malay Traditional Massage “Tusukan Siku" in treating patients with lower back pain by Visual Analogue Scale (VAS) score and Self Leg Raised (SLR) score. The MRI result will be used as an evidence of the existing of LBP in all patients. Chosen subjects will undergo two regimes of reconstructive therapy by an expert practitioner. The subjects will undergo Visual Analog Scale (VAS) test to evaluate their pain scale and Self Leg Raise (SLR) test to evaluate their physical power before and after treatment. VAS test will be performed by patients’ own rating. The VAS frame measures at a scale of 0-10. The scale indicators will be analysed as continuous variables for statistical analysis. SLR score will be measured by the orthopaedic surgeon. The patient will be lying down on his/her back and the examiner lifts the patient's leg while the knee is straight. MRI will be used to visualize detailed internal structure and limited function of the body. If proven effective this technique can be use as one of the alternative treatment for LBP. This will benefit both patients and doctors, as LBP treatment is no longer a surgical method. Such practices if proven effective can reduce the overall burden on health care system by reducing surgical procedures, and thus will reduce hospitalization due to LBP. Health care system can reduce their burden to manage the patients and the quality of life will increase in the family and society.